Comparison of Single Pulse and Double Simultaneous Pulse Laser Induced Breakdown Spectroscopy - Haider, Zuhaib (Taylor and Francis Inc., 2015)
A simple and cost-effective variant of laser induced breakdown spectroscopy is presented that involves a double simultaneous pulse configuration employing a single laser source. Its performance is compared with conventional single pulse configuration. Double simultaneous pulses were accomplished by splitting a Nd:YAG laser (1064 nm, 6 ns, 360 mJ) beam into two components that were focused on the sample surface to produce two concurrent breakdowns. Experiment was repeated for single pulse and double simultaneous pulses under different ambient pressures. The performance was evaluated on the basis of self-absorption, signal-to-noise ratio (SNR), and relative standard deviation (RSD) of the Mg II doublet (280.2704 nm, 279.553 nm). Optically thin emission lines of better profiles with higher signal-to-noise ratio resulted from double simultaneous pulses. The lowest relative standard deviations obtained by single pulse and double simultaneous pulse configurations were 18.89% and 12.01%, respectively. In fact, double simultaneous pulses have performed better than single pulse in all respects within the studied regime.